Soil improvement for sustainable environment - Harianto Rahardjo (2009)
Soil improvement for stability of trees is important for maintaining the sustainability of the “garden city” environment in Singapore. Trees have been part of urban environment and provide numerous advantages to human life. However, uprooted trees can be dangerous since they may cause damages to property (e.g., houses and vehicles) and infrastructures and may also cause injury or loss of life. The engineering properties of soil as a medium for tree growth also play an important role in tree stability. Finer-gained soils, such as top soil, have commonly been used for tree growing media. However, several cases of tree failures associated with low soil strength have occurred in Singapore. In order to enhance the soil strength for tree stability, the top soil was mixed with granite chip at different percentages. Results of the laboratory tests showed that the hydraulic properties and shear strength of the top soils changed with the addition of granite chips. The air-entry value, ψa, residual matric suction, ψr, and residual volumetric water content, Өr, of the soil mixtures decreased with the increase in the granite chip content. Beyond the air-entry value of the granite chip, the shape of SWCCs of the soil mixture of 80% granite chip and 20% top soil and the soil mixture of 50% granite chip and 50% top soil were controlled by the shape of SWCC of the top soil. The effective angle of internal friction, φ’, of the soil mixture increased by 25% (i.e., from 33o to 44o) with an addition of 50% granite chip and increased by 31% (i.e., from 33o to 48o) with an addition of 80% granite chip. The angle indicating the rate of increase in shear strength relative to the increase in matric suction, φ b, of the soil mixtures decreased with the increase in granite chip content. Field study showed that soil suctions developed near the ground surface fluctuated following the weather conditions and soil suctions decreased with depth. Assessment on the tree growth performance showed that the uncompacted top soil and in-situ soil at IMM site were the most suitable media for tree growth. The trees planted in the soil mixtures of 80% granite chip and 20% top soil and the soil mixture of 50% granite chip and 50% top soil have also shown quite good growth performance based on visual observation and results of tree girth and shoot length measurements. Theoretical modeling indicated that wind force required to cause tree instability increased with the increase in the granite chip content. The wind force at failure due to shear failure of soil (Fws) is the lowest, while the wind force at failure due to tensile failure of soil-root system (Fw tensile) is the highest. In other words, the soil-root system will most likely fail due to the shear failure of soil.